Relações entre medidas de capacidade auditiva e desempenho em tarefas de percepção da fala em crianças com deficiência auditiva - Camargo, Natália de (2013)
The purpose of the study was to establish the relationship between hearing capacity and performance on tasks of speech perception in children with hearing loss aiming at discussing factors related to effective utilization of residual hearing. Method: The procedures were performed at CeAC/DERDIC/PUCP. The Speech Intelligibility Indices (SII) were established for 55 and 65 dBSPL input sounds of ten children presenting bilateral sensorineural hearing loss, adapted with bilateral hearing aids, and which have oral language as the main mode of communication. They were submitted to a words and nonsense words repetition task either in two or three different intensities (52, 55 and 65 dBSPL). Their productions were analyzed according the criteria established by WASP Protocol and by Confusion Matrix. In the data analysis, the values of SII in the better ear were compared with the results obtained in each analysis criterion. Results: For voicing and word performance, there was a statistically significant difference between both stimuli in 55 dBSPL. For consonants, place of articulation and consonant substitution there was a statistically meaningful difference between stimuli types in 65 and 55 dBSPL and also between intensities 65 and 55 dBSPL in nonsense words. The percentage of correct words was small when compared to the percentage of correct consonants and place of articulation. Thus, the performance in the last criteria seemed more representative of the auditory capacity prescribed by SII 65, which ranged from 27% to 90% with major concentration of intermediary SII subjects. For performance of mode of articulation, there was a statistically significant difference between both words and nonsense words at 55 dBSPL and between 65 and 55 intensities in nonsense words. For performance in other error criteria, the analysis showed no statistically significant difference. Conclusion: With regards to the criterion of correct words, performance was, for most children, below the auditory capacity predicted, considering SII values. As to correct vowel performance, the investigation showed that these have ensured audibility. The criteria of performance in correct consonants and place of articulation seemed more representative of the auditory capacity anticipated by SII than the criterion of correct words performance. The performance regarding criteria of mode of articulation and voicing seem to suggest that these children were able to perceive these traits, probably due to low frequency band information. With regards to errors, the number of substitutions was higher than omissions. The characteristics of substitutions allow us to identify error orientation on certain consonant, while omissions allow for evaluating consonant audibility. Thus, the relationship between auditory capacity and performance on speech task perception cannot be considered in isolation since other factors are involved in this process, thus enabling the explanation of variability in performance. Audiological and therapeutic history, as well as linguistic and family characteristics can significantly interfere with performance given similar auditory capacity. Further studies are necessary to address these issues